ORNAMENTAL PEPPER ON REFLECTIVE BENCH UNDER PROTECTED ENVIRONMENTS - Costa, Edilson; Reche, Ranna S. R.; Silva, Abimael G. Da [UNESP]; Binotti, Flávio F. Da S.; Martins, Murilo B.; Zoz, Tiago (Associação Brasileira de Engenharia Agrícola, 2021)
Plant ambiance studies the environmental condition favorable to plant growth at the initial stage of seedlings or the complete production cycle. This study aimed to evaluate the cultivation of the ornamental pepper ‘Pyramid’ under protected environments and growing benches with and without reflective material. The protected environments consisted of a greenhouse covered with low-density polyethylene film and 42/50% shading thermo-reflective screen under the film, structure with 35% shading thermo-reflective aluminized screen, and structure with 30% shading black screen. The growing benches were tested in environments without and with reflective material made of aluminized screen. The environment of the agricultural greenhouse covered with low-density polyethylene film and 42/50% thermo-reflective screen under the film favored the growth of ornamental pepper plants regarding height and diameter and provided early flowering and high fruit production. The use of the reflective material showed no significant results for plant height, stem diameter, and the number of leaves. The use of reflective material increased the number of fruits in plants under the environments with 35% shading aluminized screen and 30% shading black screen.
Keywords: Plant ambiance; aluminized screen; Pyramid cultivar; Capsicum frutescens